Global research on ubiquitous learning: A network and output approach - Espinoza-Casco, Roque Juan; Romero-Carazas, Rafael; Quesada, Tania Quiroz; Garro-Aburto, Luzmila Lourdes; Tataje, Freddy Antonio Ochoa; Ramírez, Segundo Victor Sánchez; Torres , Magaly Chirihuana; Castillo, Consuelo del Pilar Clemente (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Ubiquitous learning refers to the advancement of online learning, adapted to the development of communication and informatics. The study aimed to carry out a bibliometric approach to ubiquitous learning worldwide indexed in Scopus from 2003 to 2023. Methodologically, it was a quantitative, bibliometric study. Scientific output indicators were generated from 2668 selected Scopus papers using English keywords ("ubiquitous" AND "learning"). From 2007 to 2023, the number of published documents increased (90.9%), indicating a growing interest in the subject of study. The United States has the highest scientific production (21%), and the CNRS Centre National de la Recherche Scientifique has the most publications (n=39). The journal IEEE Access received 2514 citations, with the author Cook, D.J. (n=532) being the most cited. It is concluded that the orientation on ubiquitous learning is dynamic and increasingly linked to the development of information and communication technologies (ICT), as this learning style uses technology to give students more independence over their learning process.
Keywords: ubiquitous learning; u-learning; bibliometrics; scientific output